2019
DOI: 10.1097/md.0000000000018047
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal irrigation vs suction alone during pediatric appendectomy for perforated appendicitis

Abstract: Background: There currently exists no substantial evidence reporting the efficacy of peritoneal irrigation in reducing the incidence of postoperative intra-abdominal abscess in pediatric patients. The purpose of our study was to perform a meta-analysis to compare rates of intra-abdominal abscess after appendectomy between irrigation and suction alone groups.Methods: We identified studies by a systematic search in EMBASE, PubMed, Web of Science, and the Cochrane Library to recognize randomized controlled trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…The use of peritoneal irrigation stems from an old principle of “dilution is the solution to pollution”. This, however, has been challenged by St Peter et al and a more recent meta-analysis, showing no benefit in preventing post-operative IAC in adults and children [ 12 , 13 ]. In a randomised prospective study conducted at our institution on adults, potential harm was indicated with irrigation [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of peritoneal irrigation stems from an old principle of “dilution is the solution to pollution”. This, however, has been challenged by St Peter et al and a more recent meta-analysis, showing no benefit in preventing post-operative IAC in adults and children [ 12 , 13 ]. In a randomised prospective study conducted at our institution on adults, potential harm was indicated with irrigation [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Irrigation of the peritoneal cavity was found to be an increasing risk of development of the intra-abdominal collection, and the pus can spread during washout from the localized area of infection in the right iliac fossa to the other compartments in the abdomen resulting in generalized peritonitis [ 47 ]. Moreover, a recent systematic review concluded that suction only is not inferior to suction and irrigation in terms of the development of the postoperative collection and the adoption of a suction-only approach may reduce the operative time [ 45 , 48 ]. Assessment of the effect of these known risk factors for the collection was not possible in this review due to the lack of data in the included studies.…”
Section: Reviewmentioning
confidence: 99%
“…Of them, 30 articles (including duplicated studies, case reports, articles without related data, review and meta-analysis publication) did not meet the inclusion criteria. The full text of 28 papers was reviewed: 11 studies were excluded (Additional file 2 : Table S1) [ 19 , 38 47 ] and 17 were selected for the meta-analysis [ 4 , 6 , 8 , 10 , 48 60 ], according to PRISMA flow diagram (Fig. 1 ).…”
Section: Main Textmentioning
confidence: 99%
“…Post-operative IAA is associated with [ 1 , 18 ] significant morbidity, patient discomfort, prolonged hospital stay and increased cost, often necessitating readmission and repeat intervention [ 7 , 19 22 ].…”
Section: Introductionmentioning
confidence: 99%